Equação do Calor com dado inicial singular - Rocha, Natã Firmino Santana (2016)
In this dissertation, we will use the techniques established in [2] to analyze the existence and uniqueness of classical solution to the nonlinear heat equation in ; provided u0 2 Lq() with some conditions on 1 q 1, where RN is a smooth bounded domain and p > 1.